Modal Analysis of Dissimilar Plate Metal Joining with Different Thickness Using MIG Welding - M. M., Hatifi; M. H., Firdaus; A. R., Yusoff (Universiti Malaysia Pahang, 2014)
This paper presents a study on the dynamic behaviour of joining hybrid part, between stainless steel and aluminium alloy by MIG welding. The objective is to analyse the effect of welding on dissimilar plate of Stainless Steel and Aluminium. The finite element model of joining between stainless steel and aluminium alloy by welding was built using a structural three-dimensional (3D) solid modelling element. Impact testing using hammer excitation and accelerometer response measuring techniques was used to measure vibration properties of hybrid parts. The natural frequency and the mode shape graph from experimental modal analysis were then compared with the results that were obtained from finite element (FE) and showed good agreement. Joining welding give effect to dynamic properties (mode shape) of modal analysis especially mode 1,3 (bending pattern) and mode 4 (second twisting). The results show significant points about the effect of MIG welding on dissimilar plate in terms of dynamic properties compared to the same material.